PENGARUH NOISE-MODULATED MONAURAL BEATS AUDITORY TERHADAP PENINGKATAN KAPASITAS MEMORI PADA LANSIA - Adre Mayza; Shella Shella; Brian Manurung (PERDOSNI, 2018)
THE EFFECTS OF NOISE-MODULATED MONAURAL BEATS AUDITORY TOWARD MEMORY CAPACITY INCREMENT OF ELDERLY PATIENTSABSTRACTIntroduction: Memory impairment is one of the disturbances of cognitive function that is often found and influential in elderly life activities. Memory impairment in elderly can be improved by applying several intervention modes, including auditory stimuli, because brain waves play a role in decreasing memory function in the elderly.Aims: To determine the effect of noise-modulated monaural beats auditory stimulation on improves memory capacity in the elderly.Methods: This study was a quasi-experiment with pre-test-post-test control group design, combining two methods of interventions; pink noise and monaural beats on alpha waves. Memory Impairment Screen (MIS) instrument were used to measure memory capacity. Subjects in this study came from the elderly population at the PELKRIS Foundation Semarang which has memory impairment based on MIS score <4.Results: There were 34 subjects of 75-90 years old with memory impairment. Most of them were women. There was significant positive effect of noise-modulated monaural beats auditory stimulation that improved memory capacity in (p<0.001) and signifiant difference of influence between treatment group and control group (p<0.001).Discussion: There were positive and significant effect of noise-modulated monaural beats auditory stimulation to improves memory capacity in elderly.Keywords: Elderly, memory, Memory Impairment Screen, monaural beats, noise stimulationABSTRAKPendahuluan: Gangguan memori merupakan salah satu masalah gangguan fungsi kognitif yang sering dihadapi para lansia dan berpengaruh dalam aktivitas kehidupan lansia. Masalah gangguan memori pada lansia dapat diatasi dengan beberapa metode intervensi, antara lain pemberian stimulus suara, karena gelombang otak berperan terhadap penurunan fungsi memori pada lansia.Tujuan: Mengetahui pengaruh stimulus noise-modulated monaural beats auditory terhadap peningkatan kapasitas memori pada lansia.Metode: Desain penelitian berupa kuasi eksperimen dengan teknik metode pre-test post-test control group design menggabungkan dua metode intervensi, yaitu penggabungan pink noise dan monaural beats pada gelombang alfa. Kapasitas memori diukur menggunakan instrumen Memory Impairment Screen (MIS). Subjek penelitian adalah populasi lansia di Yayasan PELKRIS, Semarang, yang mengalami gangguan memori berdasarkan skor MIS <4.Hasil: Didapatkan 34 subjek dengan penurunan fungsi memori yang usia terbanyak sekitar 75-90 tahun dan jumlah perempuan lebih banyak dibanding laki-laki. Terdapat pengaruh positif stimulus noise-modulated monaural beats auditory terhadap peningkatan kapasitas memori pada lansia yang signifikan (p<0,001) dan beda pengaruh antara kelompok perlakuan dan kelompok kontrol secara bermakna (p<0,001).Diskusi: Terdapat pengaruh positif dan signifikan stimulus noise-modulated monaural beats auditory terhadap peningkatan kapasitas memori pada lansia.Kata kunci: Lansia, memori, Memory Impairment Screen, monaural beats, stimulus noise